Food deprivation and hypothermia in desynchronized sleep-deprived rats - Hoshino, K. (Associação Brasileira de Divulgação Científica (ABRADIC), 1996)
Reports of the effect of desynchronized sleep (DS) deprivation on body temperature (Tb) of rats in the literature are contradictory. Since conspicuous body weight loss is common in such deprivation, the effect of food plus DS deprivation on Tb of adult male Wistar rats was studied. DS deprivation carried out by the small platform method with food ad libitum(N = 8) induced hyperthermia (Tb above 38.5 degrees C) in 1 to 3 rats daily until the 8th day, when a case of discrete hypothermia (Tb below 36.9 degrees C) appeared. Food deprivation alone started to induce hypothermia on the third day in one (20%) out of five rats. Fasting imposed from the 5th to the 8th day of DS deprivation (N = 12) caused hypothermia in 33% and 67% ofthe animals on the second and third day of starvation, respectively. DS compensatory manifestations in 6 starved rats intensified (N = 2) or precipitated (N = 2) hypothermia after the end of sleep deprivation. It is concluded that the hypothermia is not a primary effect of DS deprivation, and this state of sleep seems to have its particular functional role which is independent of thermoregulation.
Keywords: sleep deprivation; desynchronized sleep; thermoregulation; fasting; hyperthermia; hypothermia